Modelling of three phase SVPWM AC-AC converter using unity power factor control - Saidah, Saidah; Sutiksno, Hari; Purwahyudi, Bambang; Taufik, Taufik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper introduces the modelling of a novel three phase AC-AC converter with indirect use of a capacitor as DC voltage link. The proposed converter has high efficiency because it uses Space Vector PWM (SVPWM) technique at both rectificier and inverter stages to operate the pulse width modulation in IGBT switches. The novel converter is equipped with a power factor control to shape the rectifier input current waveform to be sinusoidal and to be in phase with the input voltage. To keep the DC voltage stable, the converter utilizes PI controllers. Simulations are conducted for output voltage from 120 to 300 Volts with output frequency ranging from 30 Hz to 60 Hz. The simulation results show that the converter is able to maintain stable the DC voltage and current. Furthermore, the model demonstrates the benefits of proposed converter in terms of acquiring high input power factor and sinusoidal current waveform at the output side of the inverter.